1982
DOI: 10.1038/sc.1982.12
|View full text |Cite
|
Sign up to set email alerts
|

Social and vocational reintegration of paraplegic and tetraplegic patients in Switzerland

Abstract: Abstract. A review of social and vocational reintegration statistics of 90 spinal cord injury patients admitted in 1979 is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Severe economic constraint is a common issue when dealing with SCI. 23,24 In this study, unemployment among SCI persons was very high, and majority of the caregivers did not have any paid employment. In many cases, the SCI persons were the sole breadwinners for the family before the injury.…”
Section: Discussionmentioning
confidence: 64%
“…Severe economic constraint is a common issue when dealing with SCI. 23,24 In this study, unemployment among SCI persons was very high, and majority of the caregivers did not have any paid employment. In many cases, the SCI persons were the sole breadwinners for the family before the injury.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, McGowan and Roth's (1 987) research indicated the behaviour control was seen as a problem by the significant other, however, they did find that role delineation was also a concern. Clearly, although several recent studies have shown that many SCI individuals enjoy a positive marital relationship (Crewe et al, 1979;Crewe and Krause, 1988;Deyoe, 1979;Jenik et al, 1982;Pinkerton and Griffin, 1983;Urey and Henggler, 1987;Webb et al, 1982), SCI spouses may experience considerable stress in terms of dealing with their unmet expectations and a partner who acts inappropriately in social situations.…”
Section: Discussionmentioning
confidence: 99%
“…(Forner et at., 1976;Jenik et at., 1982;Johnson et at., 1972;Pachal ski et at., 1982). He ceases to function as an individual and becomes more and more dependent on society (Sutton et at., 1982).…”
Section: Introductionmentioning
confidence: 99%